2015
DOI: 10.1103/physreva.92.052706
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic detection of atom-surface interactions in an atomic-vapor layer with nanoscale thickness

Abstract: We measure the resonance line shape of atomic vapor layers with nanoscale thickness confined between two sapphire windows. The measurement is performed by scanning a probe laser through resonance and collecting the scattered light. The line shape is dominated by the effects of Dicke narrowing, self-broadening, and atom-surface interactions. By fitting the measured line shape to a simple model we discuss the possibility to extract information about the atom-surface interaction. arXiv:1505.07004v1 [physics.atom-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 59 publications
1
15
0
1
Order By: Relevance
“…Inserting formulas (8), (9), (12) to Eq. (11) one gets for the Doppler broadened absorption profile [29] 1…”
Section: Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Inserting formulas (8), (9), (12) to Eq. (11) one gets for the Doppler broadened absorption profile [29] 1…”
Section: Theoretical Modelmentioning
confidence: 99%
“…5 caused by propagation of near-resonant light through a gas with L = λ/2 thickness with very high density [8]; 3) strong broadening and shifts of resonances, which become significant when thickness < 100 nm caused by atom-surface van der Waals interactions due to the tight confinement in the NTC [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has demonstrated that mirror spacings as narrow as 110 nm were sufficient for atom injection, [42] and recent work has demonstrated vapor cells with critical dimensions as narrow as 30 nm. [48] In addition, since these hollow channels are formed by two Bragg reflectors, they can also act as optical waveguides, possibly useful for atom trapping. [49] A second strategy for open access is to use focused ion beam (FIB) milling to remove small portions of the top Bragg reflector.…”
mentioning
confidence: 99%
“…Since most analytical treatments of quantum reflection rely on approximations, exact numerical efforts are needed to verify their regime of applicability. In parallel, matter-wave experiments enable tests of CasimirPolder interactions [19,[25][26][27][28][29][30][31][32], that require quantitative simulations to bridge the gap between theory and experiment. A recent study investigates the effect of a periodically driven surface in one dimension [33] using a phenomenological atom-surface CasimirPolder interaction potential.…”
Section: Introductionmentioning
confidence: 99%
“…the reflection of a quantum object in the absence of a classical turning point [1,2], has attracted an increasing number of studies, triggered by the developments in the field of matter-wave optics for a variety of experimental platforms [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%